Penggunaan Agregat Sungai Batu Mallopie Kabupaten Barru Sebagai Bahan Campur Beton - Alri Paembonan; Bungin, Erni Rante; Sandy, Desi (Universitas Kristen Indonesia Paulus, 2025)
Concrete is a component that is applied to construction other than wood and steel because of its advantages, resistant to fire, corrosion, durable and easy to form one of the elements of concrete formation in the form of aggregate that is easy to get, one of which is aggregate from the Batu Malopie River, Barru Regency, coarse aggregate is the main maretial element in concrete that can affect the quality of the concrete so that this study varies the size of the coarse aggregate used, namely 1